Giant viable hydatid cyst of the lung: a case report - Ghallab Nagi; Alsabahi Ali (Journal of Medical Case Reports, 2008)
Abstract Introduction Hydatid disease is a parasitic infestation caused by Echinococcus granulosus. The resulting large cysts in the lung are a special clinical entity called giant hydatid cysts. Case presentation An 18-year-old Yemeni woman presented with a dry cough and mild fever, with no history of chest pain, dyspnoea or weight loss. Chest X-ray revealed a homogenous opacity almost replacing the right lung. The patient underwent surgery which revealed a large, viable hydatid cyst measuring 26 × 18 × 5 cm. Conclusion This case report provides evidence that non-complicated hydatid cysts, even if very large, have a good prognosis and can be safely treated by parenchyma-preserving surgery.